Foraging behavior and diet composition of the gecko Phyllopezus periosus (Squamata: Phyllodactylidae) in the Brazilian semiarid Caatinga - Silva Palmeira, Cristiane Nikely (2021)
In this study, we provide new data about the foraging behavior and feeding ecology of Phyllopezus periosus, a large-sized gecko endemic from the semiarid Caatinga, northeastern Brazil, looking to answer the following questions: (1) how is the foraging mode of P. periosus? (2) Which types of prey compose its diet? (3) Are lizards selective in diet? (4) Is prey size correlated with lizard body size? The fieldwork consisted of two ten-day excursions during the dry season in the Seridó Ecological Station, state of Rio Grande do Norte. We registered foraging behavior with a voice recorder and determined movement patterns of each focal lizard. For dietary data, we used stomach flushing to obtain consumed prey items. Prey availability was estimated with sets of pitfall traps placed in the surroundings of rocky outcrops where lizards occur. Our results indicate that P. periosus is a typical sit-and-wait forager, spending most of the time immobile (proportion time moving: 1.7 ± 1.9%, number of moves per minute: 0.4 ± 0.3) and performing mainly head moves and postural adjustments. The diet was massively composed of beetles, present in 48.4% of stomachs, representing 44.4% of total prey items and 63.5% of total volume. Lizards consumed beetles in a proportion slightly higher than their proportional availability in the environment, suggesting some preference for this prey category. Males and females presented similar body sizes and did not differ in diet composition. Body size was correlated with maximum prey size, but not with minimum prey size, suggesting that lizards in this population add larger prey items to the diet while growing, but at the same time continue consuming smaller ones. In addition, records of predation upon sympatric lizards and tree sap foraging evidence that P. periosus has opportunistic feeding habits.